Avaliação proteômica e mecanismos de ação do peptídeo sintético PepGAT contra Candida albicans - Gomes, Francisco Italo Rodrigues (2025)
C. albicans is one of the main pathogenic species in humans, causing opportunistic infections that are resistant to various classes of antifungals, primarily azoles, polyenes, and echinocandins. Therefore, the search for new therapeutic alternatives is necessary. In this context, synthetic antimicrobial peptides emerge as promising alternatives, as they have a low probability of inducing antimicrobial resistance. In this study, the mechanisms of action of the synthetic peptide PepGAT, bioinspired by the chitinase of Arabidopsis thaliana, were investigated against C. albicans. A proteomic analysis was employed to determine whether PepGAT induced changes in the proteomic profile of C. albicans cells, providing insights into its effects. Additionally, enzymatic activity assays, ergosterol interaction studies, membrane permeability assessments, and combinatorial effect trial with antifungal were conducted. Proteomic analysis revealed alterations in the protein profile of C. albicans cells treated with PepGAT, affecting several key pathways involved in cell development and drug resistance. Moreover, PepGAT decreased the activity of the enzyme superoxide dismutase (SOD) while increasing catalase (CAT) activity, suggesting an impact on the cellular redox system. In the ergosterol interaction assay, PepGAT-treated cells exhibited a loss of activity, indicating a possible interaction between PepGAT and exogenous ergosterol. Fluorescence microscopy showed an increase in cell membrane permeability, evidenced by the formation of pores of at least 6 kDa. Additionally, synergy assays demonstrated that PepGAT enhanced the action of ITR at certain concentrations. These findings indicate that PepGAT exhibits multiple mechanisms of action against C. albicans, highlighting its potential as an alternative antifungal agent.